Stem-cells: A contemporary perspective (Research, Society and Development, 2024)
Research carried out using stem cells from exfoliated primary teeth (SHED) has gained prominence in recent decades. The use became promising due to the lower ethical implications and regulatory aspects of collection and use, as well as the lower risk of damage to the donor and versatility of use, also because they have a wide possibility of multiplication even though they are non-specific.  Since they present positive results (in vitro and in vivo) in the treatment of neurodegenerative, congenital and acquired diseases. Also highlighting the importance of the dental surgeon, since the benefits and application are not restricted to dental use, but in scientific and medical areas in general.  This work aimed to carry out a literature review without meta-analysis, with the purpose of correlating current articles on the use of SHED. Use will also be discussed in injuries to muscular, nervous, and hepatic tissues in the treatment of degenerative diseases.